Green high-hardness heat-resistant glassware and preparation method thereof
By introducing FeSi2 nanocrystals and Al4B2O9 nanofibers into the glass, combined with annealing and tempering, the problem of insufficient hardness and heat resistance of high-hardness heat-resistant glassware is solved, significantly improving its performance and stability under extreme conditions .
Patent Information
- Application Number
- CN202411349374.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing high-hardness heat-resistant glassware still has room for improvement in hardness and heat resistance, especially when used under extreme conditions.
In-situ growth technology is used to introduce FeSi2 nanocrystals and Al4B2O9 nanofibers into the glass, and combined with annealing and tempering treatment, the hardness and heat resistance of the glassware are improved. FeSi2 nanocrystals improve hardness by enhancing interface interactions and layered structures, Al4B2O9 nanofibers improve binding strength and thermal stability through high aspect ratio and small diameter, annealing treatment releases internal stress, and tempering treatment enhances surface compression stress.
It significantly improves the hardness, heat resistance and stability of glassware, making it more durable and reliable in high-temperature environments, and is suitable for harsh application scenarios of high temperature, high pressure and mechanical wear.
Smart Images

Figure CN118851568B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of glass materials, and in particular to a green high-hardness heat-resistant glassware and a preparation method thereof. Background Art
[0002] In modern scientific research, laboratory operations, industrial production and other fields, high hardness heat-resistant glassware is an indispensable experimental tool. These utensils have excellent heat resistance and high hardness, and can withstand use under extreme conditions such as high temperature, high pressure and strong acid and alkali, ensuring the accuracy and safety of the experiment. In the field of scientific research, high hardness heat-resistant glassware is widely used in chemical synthesis, material analysis, biomedical experiments and other experimental processes. In laboratory operations, high hardness heat-resistant glassware is particularly important for withstanding high temperatures and strong acid and alkali solutions. In industrial production, high hardness heat-resistant glassware is widely used in the production process of chemical, pharmaceutical, food and other industries. In summary, high hardness heat-resistant glassware plays an important role in scientific research, laboratory operations and industrial production. Its excellent heat resistance and high hardness can meet the use requirements under various extreme conditions and promote the progress of scientific research and industrial production.
[0003] At present, the development of high-hardness and heat-resistant glassware has achieved remarkable results, but there are still some shortcomings, which are mainly reflected in the following aspects. (1) The hardness of glassware still needs to be further improved to meet the requirements of more demanding use environments. For example, the Chinese patent with publication number CN108083635A discloses a silicon dioxide-based tempered glass, but since the glass is entirely amorphous, this limits the further improvement of its hardness. (2) The heat resistance still needs to be improved. For example, the Chinese patent with publication number CN110563331A discloses a high borosilicate glass, which mainly uses boron oxide to improve its heat resistance, but it is still based on the amorphous matrix of the glass itself, and there is no other microstructure to enhance heat resistance. Therefore, glassware currently still faces many challenges in terms of hardness and heat resistance. In order to fill this technical gap, it is necessary to develop a new type of glassware that has both high hardness and heat resistance to meet the needs of high-performance glassware. Summary of the invention
[0004] (1) Technical problems solved
[0005] The purpose of the present invention is to provide a green high-hardness heat-resistant glassware and a preparation method thereof, so as to solve the problem that the current glassware is insufficient in hardness and heat resistance.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A green high-hardness heat-resistant glassware is made from the following raw materials in parts by weight: 55.0-72.0 parts of silicon dioxide, 8.0-18.0 parts of sodium oxide, 6.0-15.0 parts of aluminum oxide, 2.0-4.0 parts of potassium oxide, 3.0-10.0 parts of boron oxide, 0.2-2.0 parts of magnesium oxide, 0.2-1.5 parts of calcium oxide, 0.3-1.2 parts of zinc oxide, 7.0-15.0 parts of sodium fluorosilicate, 0.6-2.0 parts of iron oxide, 0.2-1.0 parts of chromium oxide, 0.1-0.4 parts of vanadium oxide, 0.2-0.4 parts of lithium oxide and 0.6-1.6 parts of silicon powder;
[0009] The green high-hardness heat-resistant glassware contains 5-10% volume fraction of in-situ grown FeSi2 nanocrystals;
[0010] The average diameter of the FeSi2 nanocrystals is 4-8 nm;
[0011] The FeSi2 nanocrystals contain stacking fault structures;
[0012] The green high-hardness heat-resistant glassware contains 2-8% volume fraction of in-situ grown Al4B2O9 nanofibers;
[0013] The Al4B2O9 nanofibers have an average diameter of 200-550nm and a length of 800-1500nm;
[0014] The preparation method of the green high-hardness heat-resistant glassware comprises the following steps:
[0015] S1: Mixing and melting: weigh the raw materials according to the above proportions, mix them evenly, and then add them into a high-temperature melting furnace to melt the raw materials at high temperature;
[0016] S2: Molding process: the raw materials melted in S1 are molded by centrifugation or pressing to obtain molded products;
[0017] S3: Annealing treatment: annealing the molded product obtained in S2;
[0018] S4: Tempering treatment: The molded product after annealing in S3 is cooled to room temperature, and then tempered to finally obtain a green, high-hardness, heat-resistant glassware.
[0019] The present invention aims to significantly improve the hardness and heat resistance of glassware by designing and in-situ growing FeSi2 nanocrystals in glassware. First, FeSi2 is self-generated in-situ by silicon powder and iron oxide at high temperature. The FeSi2 nanocrystals, with their grain size of 4 to 8 nm, enhance the interaction between crystal interfaces, thereby greatly improving the hardness of the material. Compared with the externally added nanocrystals, its in-situ growth characteristics bring stronger interface compatibility and bonding strength, thereby significantly improving the hardness of the glassware. In addition, the stacking fault structure contained in the nanocrystals further enhances its hardness, which plays a vital role in enhancing the hardness of the glassware. In terms of heat resistance, the in-situ grown FeSi2 nanocrystals also perform well. The strong interface bonding formed between the nanocrystals and the glass matrix not only enhances the overall strength and stability of the vessel, but also enables it to better cope with the stress generated by thermal expansion and cooling in a high temperature environment, greatly reducing the risk of cracking. It is worth mentioning that the stacking fault structure inside the nanocrystals not only increases the number of grain boundaries, enhances the strength and toughness of the material, but also has good thermal stability in a high temperature environment. This makes the glassware more stable in high temperature environments and less likely to deform or break. In summary, the in-situ grown FeSi2 nanocrystals significantly improve the hardness and heat resistance of glassware with their strong interface bonding and unique stacking fault structure. This innovative technology significantly improves the stability, durability and reliability of glassware in high temperature environments and is suitable for various high temperature application scenarios.
[0020] The present invention adopts in-situ growth technology to introduce Al4B2O9 nanofibers, aiming to significantly optimize and enhance the hardness and heat resistance of glassware by utilizing its unique high aspect ratio characteristics. The following is an analysis of the specific impact of the high aspect ratio of nanofibers on the performance of glassware: In terms of hardness enhancement, the in-situ grown Al4B2O9 nanofibers significantly enhance the bonding strength with the glass matrix by virtue of their high aspect ratio. This enhanced bonding force not only effectively resists the action of external forces, but also evenly disperses stress and avoids local stress concentration. At the same time, the small diameter and high specific surface area of the nanofibers further promote the interaction between the grain boundaries, thereby greatly improving the hardness of the glassware. This makes the glassware outstanding in resisting scratches and wear, greatly improving its durability. In terms of heat resistance improvement, the high aspect ratio of Al4B2O9 nanofibers also plays a key role. Its small diameter and high specific surface area effectively slow down the heat conduction rate, so that the thermal expansion and thermal stress of the glassware in a high temperature environment are effectively controlled. This slowed heat conduction also reduces the rapid loss of heat, which helps to maintain the shape stability of the glassware. In high temperature environments, nanofibers significantly reduce the risk of deformation and breakage of glassware, greatly improving its heat resistance. In summary, the high aspect ratio of Al4B2O9 nanofibers has a profound effect on the hardness and heat resistance of glassware. Its enhanced bonding strength, ability to disperse stress and slow down heat conduction make glassware outstanding in hardness and heat resistance, and suitable for a variety of harsh application scenarios with high temperature, high pressure and mechanical wear. Therefore, the introduction of Al4B2O9 nanofibers using in-situ growth technology has shown great potential and broad application prospects in improving the performance of glassware.
[0021] Furthermore, the high temperature melting temperature of step S1 is 1450-1550°C.
[0022] Furthermore, the annealing temperature of step S3 is 520-600° C., and the annealing time is 40-90 min.
[0023] Furthermore, during the tempering treatment in step S4, the molded product is slowly heated to 590-630°C at a heating rate of 0.4-2°C / min, and the heat preservation time is 30-60min, and then quickly cooled to room temperature by strong wind at a cooling rate of 20-50°C / s.
[0024] Furthermore, the glassware after the tempering treatment in step S4 has a green appearance, a surface Mohs hardness of 6.5-7.5, and a thermal shock resistance of ≥150°C.
[0025] The purpose of the present invention to anneal and then temper the glassware is to enhance the strength, heat resistance and safety of the glassware. The mechanism of annealing is to release and adjust the internal stress by heating the glassware to a certain temperature and then slowly cooling it. During the manufacturing process, the glassware undergoes a rapid cooling process, resulting in an uneven internal molecular structure and stress. These internal stresses will weaken the strength and heat resistance of the glass. Through annealing, the molecular structure of the glassware is rearranged, and the internal stress is released, thereby improving the stability and heat resistance of the vessel. The mechanism of tempering is to heat the glassware to a high temperature and then quickly cool it, so that compressive stress is formed on the surface and tensile stress is formed inside. This stress distribution enhances the strength of the glassware. When an external force acts on the glassware, the compressive stress on the surface will resist the external force, making the glass more difficult to break. Even if the glassware breaks, the internal tensile stress will cause the glass fragments to be small particles, reducing the risk of injury to the user. In summary, the performance and safety of glassware can be improved by first annealing to eliminate internal stress and then tempering to enhance the strength and heat resistance of glassware. This treatment method not only makes glassware more durable and able to withstand greater pressure and temperature changes, but also reduces the risk of injury to users when the glass breaks, improving its reliability and safety.
[0026] (3) Beneficial technical effects
[0027] The present invention proposes three innovative technologies for improving the hardness and heat resistance of glassware. First, the hardness and heat resistance of glassware are significantly improved by in-situ growth of FeSi2 nanocrystals in the glassware. The 4-8nm grain size and in-situ growth characteristics of the nanocrystals enhance the interface compatibility and bonding strength, and the stacking fault structure further enhances the hardness, making the glassware stable, durable and reliable in high temperature environments. Secondly, Al4B2O9 nanofibers are introduced into glassware using in-situ growth technology. Their high aspect ratio characteristics enhance the bonding strength with the glass matrix, effectively disperse stress and improve hardness, while slowing down the heat conduction speed, controlling thermal expansion and thermal stress, so that the glassware can still maintain excellent performance in harsh environments. Finally, the present invention adopts the annealing and then tempering treatment technology, which releases and adjusts the internal stress through annealing, improves stability and heat resistance, and the tempering treatment enhances the strength of the vessel and reduces the risk of injury when broken. This treatment method significantly improves the performance, reliability and safety of glassware, making it more durable and able to withstand greater pressure and temperature changes. The final glassware has a green appearance, a surface Mohs hardness of 6.5~7.5, and thermal shock resistance ≥150℃, further confirming its excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1This is the XRD phase analysis diagram of the glassware prepared in Example 1 of the present invention.
[0029] Figure 2 This is a transmission electron microscope photograph of the nano-FeSi2 and Al4B2O9 nanofibers prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0031] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0032] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies
[0033]
[0034] Example 1
[0035] A green high-hardness heat-resistant glassware is made of the following raw materials in parts by weight: 55.0 parts of silicon dioxide, 8.0 parts of sodium oxide, 6.0 parts of aluminum oxide, 2.0 parts of potassium oxide, 3.0 parts of boron oxide, 0.2 parts of magnesium oxide, 0.2 parts of calcium oxide, 0.3 parts of zinc oxide, 7.0-15.0 parts of sodium fluorosilicate, 0.6 parts of iron oxide, 0.2 parts of chromium oxide, 0.1 parts of vanadium oxide, 0.2 parts of lithium oxide and 0.6 parts of silicon powder;
[0036] The green high-hardness heat-resistant glassware contains 2% volume fraction of in-situ grown FeSi2 nanocrystals;
[0037] The average diameter of the FeSi2 nanocrystals is 4 nm.
[0038] The above-mentioned FeSi2 nanocrystals contain stacking fault structures;
[0039] The green high-hardness heat-resistant glassware contains 2% volume fraction of in-situ grown Al4B2O9 nanofibers;
[0040] The Al4B2O9 nanofibers mentioned above have an average diameter of 200 nm and a length of 800 nm;
[0041] The preparation method of the above green high-hardness heat-resistant glassware comprises the following steps:
[0042] S1: Mixing and melting: weigh the raw materials according to the above proportions, mix them evenly, and then add them into a high-temperature melting furnace to melt the raw materials at high temperature;
[0043] S2: Molding process: the melted raw materials in S1 are molded by centrifugation to obtain molded products;
[0044] S3: Annealing treatment: annealing the molded product obtained in S2;
[0045] S4: Tempering treatment: The molded product after annealing in S3 is cooled to room temperature, and then tempered to finally obtain a green, high-hardness, heat-resistant glassware.
[0046] The high temperature melting temperature in the above step S1 is 1450°C.
[0047] The annealing temperature in the above step S3 is 520° C. and the annealing time is 40 min.
[0048] During the tempering treatment in step S4, the molded product is slowly heated to 590°C at a heating rate of 0.4°C / min, kept warm for 30 minutes, and then rapidly cooled to room temperature by strong wind at a cooling rate of 20°C / s.
[0049] The glassware after the tempering treatment in step S4 has a green appearance, a surface Mohs hardness of 6.5, and a thermal shock resistance of 161°C.
[0050] Example 2
[0051] A green high-hardness heat-resistant glassware is made of the following raw materials in parts by weight: 60 parts of silicon dioxide, 10 parts of sodium oxide, 8 parts of aluminum oxide, 3 parts of potassium oxide, 4 parts of boron oxide, 0.6 parts of magnesium oxide, 0.5 parts of calcium oxide, 0.6 parts of zinc oxide, 9 parts of sodium fluorosilicate, 0.8 parts of iron oxide, 0.4 parts of chromium oxide, 0.2 parts of vanadium oxide, 0.3 parts of lithium oxide and 0.8 parts of silicon powder;
[0052] The green high-hardness heat-resistant glassware contains 3% volume fraction of in-situ grown FeSi2 nanocrystals;
[0053] The average diameter of the FeSi2 nanocrystals is 5 nm.
[0054] The above-mentioned FeSi2 nanocrystals contain stacking fault structures;
[0055] The green high-hardness heat-resistant glassware contains 4% volume fraction of in-situ grown Al4B2O9 nanofibers;
[0056] The Al4B2O9 nanofibers have an average diameter of 250 nm and a length of 1000 nm;
[0057] The preparation method of the above green high-hardness heat-resistant glassware comprises the following steps:
[0058] S1: Mixing and melting: weigh the raw materials according to the above proportions, mix them evenly, and then add them into a high-temperature melting furnace to melt the raw materials at high temperature;
[0059] S2: Molding process: The melted raw materials in S1 are pressed and molded to obtain molded products;
[0060] S3: Annealing treatment: annealing the molded product obtained in S2;
[0061] S4: Tempering treatment: The molded product after annealing in S3 is cooled to room temperature, and then tempered to finally obtain a green, high-hardness, heat-resistant glassware.
[0062] The high temperature melting temperature in step S1 is 1480°C.
[0063] The annealing temperature of step S3 is 540° C. and the annealing time is 50 min.
[0064] During the tempering treatment in step S4, the molded product is slowly heated to 600°C at a heating rate of 0.6°C / min, and kept at a temperature for 40 minutes, and then rapidly cooled to room temperature by strong wind at a cooling rate of 30°C / s.
[0065] The glassware after the tempering treatment in step S4 has a green appearance, a surface Mohs hardness of 6.7, and a thermal shock resistance of 169°C.
[0066] Example 3
[0067] A green high-hardness heat-resistant glassware is made of the following raw materials in parts by weight: 65 parts of silicon dioxide, 12 parts of sodium oxide, 11 parts of aluminum oxide, 3 parts of potassium oxide, 6 parts of boron oxide, 1.4 parts of magnesium oxide, 1.1 parts of calcium oxide, 1 part of zinc oxide, 11 parts of sodium fluorosilicate, 1.3 parts of iron oxide, 0.8 parts of chromium oxide, 0.3 parts of vanadium oxide, 0.3 parts of lithium oxide and 1.2 parts of silicon powder;
[0068] The green high-hardness heat-resistant glassware contains 3% volume fraction of in-situ grown FeSi2 nanocrystals;
[0069] The average diameter of the FeSi2 nanocrystals is 6 nm.
[0070] The above-mentioned FeSi2 nanocrystals contain stacking fault structures;
[0071] The green high-hardness heat-resistant glassware contains 6% volume fraction of in-situ grown Al4B2O9 nanofibers;
[0072] The Al4B2O9 nanofibers have an average diameter of 450 nm and a length of 1200 nm;
[0073] The preparation method of the above green high-hardness heat-resistant glassware comprises the following steps:
[0074] S1: Mixing and melting: weigh the raw materials according to the above proportions, mix them evenly, and then add them into a high-temperature melting furnace to melt the raw materials at high temperature;
[0075] S2: Molding process: The melted raw materials in S1 are pressed and molded to obtain molded products;
[0076] S3: Annealing treatment: annealing the molded product obtained in S2;
[0077] S4: Tempering treatment: The molded product after annealing in S3 is cooled to room temperature, and then tempered to finally obtain a green, high-hardness, heat-resistant glassware.
[0078] The high temperature melting temperature in step S1 is 1500°C.
[0079] The annealing temperature in the above step S3 is 580° C. and the annealing time is 80 min.
[0080] During the tempering treatment in step S4, the molded product is slowly heated to 610°C at a heating rate of 1.6°C / min, and kept warm for 50 minutes, and then rapidly cooled to room temperature by strong wind at a cooling rate of 40°C / s.
[0081] The glassware after the tempering treatment in step S4 has a green appearance, a surface Mohs hardness of 6.8, and a thermal shock resistance of 172°C.
[0082] Example 4
[0083] A green high-hardness heat-resistant glassware is made of the following raw materials in parts by weight: 72.0 parts of silicon dioxide, 18.0 parts of sodium oxide, 15.0 parts of aluminum oxide, 4.0 parts of potassium oxide, 10.0 parts of boron oxide, 2.0 parts of magnesium oxide, 1.5 parts of calcium oxide, 1.2 parts of zinc oxide, 15.0 parts of sodium fluorosilicate, 2.0 parts of iron oxide, 1.0 parts of chromium oxide, 0.4 parts of vanadium oxide, 0.4 parts of lithium oxide and 1.6 parts of silicon powder;
[0084] The green high-hardness heat-resistant glassware contains 6% volume fraction of in-situ grown FeSi2 nanocrystals;
[0085] The average diameter of the FeSi2 nanocrystals is 8 nm.
[0086] The above-mentioned FeSi2 nanocrystals contain stacking fault structures;
[0087] The green high-hardness heat-resistant glassware contains 8% volume fraction of in-situ grown Al4B2O9 nanofibers;
[0088] The Al4B2O9 nanofibers have an average diameter of 550 nm and a length of 1500 nm;
[0089] The preparation method of the above green high-hardness heat-resistant glassware comprises the following steps:
[0090] S1: Mixing and melting: weigh the raw materials according to the above proportions, mix them evenly, and then add them into a high-temperature melting furnace to melt the raw materials at high temperature;
[0091] S2: Molding process: the melted raw materials in S1 are molded by centrifugation to obtain molded products;
[0092] S3: Annealing treatment: annealing the molded product obtained in S2;
[0093] S4: Tempering treatment: The molded product after annealing in S3 is cooled to room temperature, and then tempered to finally obtain a green, high-hardness, heat-resistant glassware.
[0094] The high temperature melting temperature in step S1 is 1550°C.
[0095] The annealing temperature in the above step S3 is 600° C. and the annealing time is 90 min.
[0096] During the tempering treatment in step S4, the molded product is slowly heated to 630°C at a heating rate of 2°C / min, and kept warm for 60min, and then rapidly cooled to room temperature by strong wind at a cooling rate of 50°C / s.
[0097] The glassware after the tempering treatment in step S4 has a green appearance, a surface Mohs hardness of 7.4, and a thermal shock resistance of 176°C.
[0098] Example 5
[0099] It is basically the same as Example 1, except that the silicon powder in the preparation raw material is 1.6 parts, and the volume fraction of the generated FeSi2 nanocrystals is 10%.
[0100] Comparative Example 1
[0101] The method is basically the same as Example 1, except that silicon powder is not added to the raw materials, so there is no FeSi2 nanocrystal in the glass container.
[0102] Comparative Example 2
[0103] It is basically the same as Example 1, except that no alumina is added to the raw material, so Al4B2O9 nanofibers are not generated.
[0104] Comparative Example 3
[0105] The method is basically the same as Example 1, except that the glassware is not subjected to S4 tempering treatment.
[0106] Characterization Tests:
[0107] X-ray diffraction (XRD) was used to characterize the physical properties of the glassware prepared in the present invention 1. Figure 1 The diffraction peaks of FeSi2 nanocrystals and Al4B2O9 crystalline phases can be clearly seen, proving that the glassware contains these two phases.
[0108] The microstructure of the glassware prepared in Example 1 was characterized by transmission electron microscopy. Figure 2 This is a transmission electron microscope photograph of the nano-FeSi2 and Al4B2O9 nanofibers prepared in Example 1 of the present invention. In the left side of the figure, the Al4B2O9 nanofibers with a relatively long length diameter can be clearly seen, and the in-situ grown nano-FeSi2 crystals can be clearly seen next to the nanofibers, and then inside the crystals, it can be clearly seen that the nanocrystals contain stacking fault structures.
[0109] Performance Test:
[0110] Hardness is one of the important indicators in glass applications. The method of using a Vickers hardness tester to test the hardness of glassware is as follows: First, place the glassware on a flat hardness test stand to ensure that the bottom of the vessel is in full contact. Then, adjust the test depth of the Vickers hardness tester, which is usually 1 / 10 of the thickness of the vessel. Next, gently place the indenter of the Vickers hardness tester on the surface of the vessel, perpendicular to the surface, and gradually increase the pressure until the indenter penetrates the vessel. The Vickers hardness tester will display a number indicating the test result. The larger the number, the harder the vessel. Finally, record the test results and clean the instrument for next use. During the test, avoid using excessive pressure, pay attention to the impact of ambient temperature and humidity on the test results, and perform multiple tests to take the average value to improve accuracy.
[0111] Resistance to thermal shock: refer to GB15763.2-2005, place 300mm×300mm glassware samples in ovens at different temperatures, keep warm for more than 4 hours, take out and immediately immerse the samples vertically in a mixture of ice and water at 0℃, and ensure that more than 1 / 3 of the height of the samples can be immersed in water. After 5 minutes, observe whether the glass is damaged. The fish-scale peeling on the surface and edge of the glass should not be regarded as damage. Then test the damage at different temperatures, and record the highest temperature at which the glassware is not damaged as the thermal shock temperature T.
[0112] The hardness and thermal shock resistance of the glasses of Examples 1 to 5 and Comparative Examples 1 to 3 are summarized in Table 2.
[0113] Table 2 Performance of glass of Examples 1 to 5 and Comparative Examples 1 to 3
[0114]
[0115] The main difference between Comparative Example 1 and Example 1 is whether the glassware contains FeSi2 nanocrystals. It can be seen from Table 2 that FeSi2 nanocrystals can significantly improve the hardness and heat resistance of glassware.
[0116] The main difference between Comparative Example 3 and Example 1 is whether the glassware is tempered. From Table 2, it can be seen that tempering can significantly improve the hardness and heat resistance of the glassware.
[0117] In summary, the FeSi2 nanocrystals, Al4B2O9 nanofibers and tempering treatment designed in the present invention can significantly improve the hardness and heat resistance of glassware, and can provide excellent performance and effects in multiple fields.
[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing green high-hardness heat-resistant glassware, characterized in that: The following steps are involved: S1: Mixing and melting: weigh the raw materials according to the proportion, mix them evenly, and then add them into a high-temperature melting furnace to melt the raw materials at high temperature; S2: Molding process: the raw materials melted in S1 are molded by centrifugation or pressing to obtain molded products; S3: Annealing treatment: annealing the molded product obtained in S2; S4: Tempering treatment: The molded product after annealing in S3 is cooled to room temperature, and then tempered to finally obtain a green, high-hardness, heat-resistant glassware; The green high-hardness heat-resistant glassware is made of the following raw materials in parts by weight: 55.0-72.0 parts of silicon dioxide, 8.0-18.0 parts of sodium oxide, 6.0-15.0 parts of aluminum oxide, 2.0-4.0 parts of potassium oxide, 3.0-10.0 parts of boron oxide, 0.2-2.0 parts of magnesium oxide, 0.2-1.5 parts of calcium oxide, 0.3-1.2 parts of zinc oxide, 7.0-15.0 parts of sodium fluorosilicate, 0.6-2.0 parts of iron oxide, 0.2-1.0 parts of chromium oxide, 0.1-0.4 parts of vanadium oxide, 0.2-0.4 parts of lithium oxide and 0.6-1.6 parts of silicon powder; The green high-hardness heat-resistant glassware contains 2-6% volume fraction of in-situ grown FeSi2 nanocrystals; The FeSi2 nanocrystals contain stacking fault structures; The green high-hardness heat-resistant glassware contains 2-8% volume fraction of in-situ grown Al4B2O9 nanofibers.
2. A green high-hardness heat-resistant glassware as claimed in claim 1, characterized in that: The average diameter of the FeSi2 nanocrystals is 4-8 nm.
3. The green high-hardness heat-resistant glassware according to claim 1, characterized in that: The Al4B2O9 nanofibers have an average diameter of 200-550 nm and a length of 800-1500 nm.
4. The method for preparing a green high-hardness heat-resistant glassware according to claim 1, characterized in that: The high temperature melting temperature of S1 is 1450~1550℃.
5. The method for preparing a green high-hardness heat-resistant glassware according to claim 1, characterized in that: The annealing temperature of S3 is 520-600° C., and the annealing time is 40-90 min.
6. The method for preparing a green high-hardness heat-resistant glassware according to claim 1, characterized in that: During the S4 tempering treatment, the molded product is slowly heated to 590-630°C at a heating rate of 0.4-2°C / min, kept warm for 30-60min, and then rapidly cooled to room temperature at a cooling rate of 20-50°C / s.
7. The method for preparing a green high-hardness heat-resistant glassware according to claim 1, characterized in that: The surface Mohs hardness of the glassware after S4 tempering treatment is 6.5-7.5, and the thermal shock resistance is ≥150°C.
Citation Information
Patent Citations
High-hardness toughened glass mobile phone pasting film
CN108083635A
High borosilicate glass
CN110563331A
Heatproof microcrystalline glassware formula and manufacturing technology thereof
CN106630647A
Glass ceramic, preparation method thereof and glass ceramic product
CN116102259A